Distributed temperature–strain sensor based on inter-mode Kerr four-wave mixing of PMF: proposal and proof-of-concept. (1st July 2022) - Liu, Li-Ming; Yang, Yu-Lian; Deng, Qing-Xue; Jia, Xin-Hong; Liang, Wen-Yan; Jiang, Li; Song, Wei-Jie; Zhang, Xuan
Abstract: A novel concept of distributed temperature–strain sensors is proposed using inter-mode Kerr four-wave mixing of polarization-maintaining fiber (PMF), in which the dominated physical mechanism is basically different from reported Brillouin dynamic grating (BDG). The independent measurement for temperature and strain sensitivities (−0.431 MHz °C −1 and 0.067 MHz/10 με ) was completed by detecting the change in birefringence under pump-Stokes frequency separation at 370 MHz. As a preliminary proof-of-concept, sensing with a spatial resolution of ∼5 m was demonstrated along ∼210 m PMF. Compared with BDG, the proposed sensor features potential of multiple parameters measurement including temperature–strain and liquid acoustic impedance.